Global Salafisme antara Gerakan dan Kekerasan - Muzammil, Iffah (Program Studi Filsafat Agama Fakultas Ushuluddin dan Filsafat UIN Sunan Ampel Surabaya, 2013)
This article explores Salafism movement between ideology and violence. Categorically, salafi movement can be categorized in two forms. First, salafi. This group berorintasi the purification of faith to make improvements through individual, family, and community structure. Second, salafi jihadi. Although this group also aims to purification, but this group tends to be politically, do not even hesitate to commit violence. However, they both have the desire to realize a people as a form of community of believers. In the end, according to Bernard Haykel, Salafism least understood of the three basic constitution. First, theology embodied in the doctrine of monotheism. In matters of theology, all members of this movement looks unanimously agreed. Second, the law, which pivots on the issue of ijtihad. Although there are differences in attitude, but most of the salafi found ijtihad is a necessity, while taqlîd should be avoided, even by Muslims who are not educated though. Third, the political, which is determined by the methodology of their choice to realize the desire involved in the international arena.